(untitled) (World Economics and Finance Bulletin, 2023)
In this paper have been investigated problems of ensuring the economic sustainability of industrial enterprises, developed a methodology for assessing the economic sustainability of industrial enterprises, analyzed the current state of the economic sustainability of industrial enterprises in our country, developed a methodology for ensuring the economic sustainability of industrial enterprises of the Republic of Uzbekistan, especially chemical industry enterprises, based on a deep study of the experience of advanced foreign countries, scientific proposals and practical recommendations for improvement are substantiated